A relevância da ética teológico-filosófica cristã para o processo de produção de informações pelo profissional contabilista - Nascimento, Cleber José (2014)
The goal of this work is to show the importance of Christian theological philosophical ethics for the exercise of the profession of accountant, in generating and producing information, through the data related to the accounting fact, as well as its importance for society, especially in the business and political spheres. The concept of theological-philosophical reflection of ethics was described as a moral science, associating these concepts with the context of the work of the professional accountant, as well as with ethical issues in the exercise of the profession and of the individual ethics which govern human behavior. The methodology utilized made use of bibliographical research in specific literature, contained in books and articles on the theme. Through the study it could be observed that the Christian theological-philosophical ethic presupposes themes and certain duties which individuals have toward their equals, in daily life, and that the ethical reflection is, in great measure, conditioned by traditions, habits and customs of the context of which the thinking subject is part as a social being. It was verified that it is necessary for the professional accountant to carry out his/her role in an ethical manner, without this meaning the loss of his/her autonomous capacity to reflect about the concrete and sporadic problems, since the activity of the accountant is characterized, fundamentally, by providing services, which constitute furnishing information and evaluations of physical, economic and financial nature, about the patrimony of businesses and also of persons. In this way the task of reflective ethical exercise is imposed on the professional accountant according to the norms dictated by the legal exercise of the profession, so as to not succumb to the organizational logics of pure financialization interest which has dominated the globalization processes of the last three decades.